Ecological-Economic Analysis of Wetlands - R.K. Turner; J.C.J.M. van den Bergh; A. Barendregt; E. Maltby (Tinbergen Institute, 1998)
Wetlands all over the world have been lost or are threatened in spite of various international agreements and national policies. This is caused by: (1) the public nature of many wetlands products and services; (2) user externalities imposed on other stakeholders; and (3) policy intervention failures that are due to a lack of consistency among government policies in different areas (economics, environment, nature protection, physical planning, etc.). All three causes are related to information failures which in turn can be linked to the complexity and `invisibility' of spatial relationships among groundwater, surface water and wetland vegetation. Integrated wetland research combining social and natural sciences can help in part to solve the information failure to achieve the required consistency across various government policies. An integrated wetland research framework suggests that a combination of economic valuation, integrated modelling, stakeholder analysis, and multi-criteria evaluation can provide complementary insights into sustainable and welfare-optimising wetland management and policy. Subsequently, each of the various components of such integrated wetland research is reviewed and related to wetland management policy.
Keywords: 330; Cost-benefit analysis; Ecological-economic wetland modelling; Valuation of wetland goods and services; Hydrology; Multi-criteria evaluation; Stakeholders; Feuchtgebiet; Umweltökonomik; Theorie